Needs Analysis for the Development of Web-Based Learning Multimedia Context Climate Change Issues Environmental Issues Content to Support Junior High School Students' Literacy - Zulaiha, Zulaiha; Hartono, Hartono; Siahaan, Sardianto Markos (Journal of Innovation and Research in Primary Education, 2025)
Global warming and climate change represent critical contemporary challenges requiring enhanced environmental literacy among students. Despite technological advancement in education, conventional learning media remain insufficient to address junior high school students' needs for interactive and engaging environmental education, particularly regarding climate change issues. This research and development study employed the Alessi and Trollip model to conduct comprehensive needs analysis for web-based multimedia development. Data were collected through field observations, semi-structured interviews, and questionnaires distributed to 210 teachers and 623 students across South Sumatra province during the 2024/2025 academic year. Quantitative data were analyzed using descriptive statistics with 5-point Likert scales, while qualitative data underwent thematic analysis to identify user needs and preferences. Findings revealed substantial demand for web-based learning multimedia, with 93% of teachers expressing strong need for interactive materials and 91% confirming enhanced student motivation through interactive website-based media. Student data showed 51% familiarity with website-based platforms and 42% strong desire for interactive learning approaches. However, 48% of students frequently experienced comprehension difficulties with current materials. Two primary practicality factors emerged: pedagogical factors (curriculum alignment and learning needs) and technical factors (infrastructure, accessibility, and usage guidance). Learning style analysis revealed visual learner dominance (60%), followed by auditory (25%) and kinesthetic learners (15%). Results demonstrate urgent need for innovative educational media integrating environmental content with web-based technology. The study provides evidence-based foundations for needs-driven multimedia development, contributing to educational technology literature and environmental education pedagogy. Future research should explore implementation effectiveness and long-term impacts on environmental literacy development.